Gross Variants of Fetal Membranes in Healthy Placentae among Females in Pakistan - Aneeqa Chughtai, Yasmeen Bashir, Saira Munawar, Humara Gul, Zaffar Iqbal Malik, Amjad Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: It is done to find out the gross variants of fetal membranes in healthy placentae among local females to define the variations found among uneventful pregnancies. Study design: This is a cross-sectional study. Place and Duration of Study: The study was done at Department of Anatomy, CMH Kharian Medical College. Kharian, from February 2023 to July 2023. Introduction: Fetal membranes are extraembryonic tissue that include the amnio-chorion. It is considered as an appendage attached to the margin of placental disc. Normally, it is avascular, thin, shiny and translucent structure with great tensile strength and elasticity, though has a short life-span. It has the same genetic composition as the fetus. Placenta membranecae is one having vessels in the smooth chorion and circumvallate placentae in which the membranes are grooved into the disc partially or incompletely are seen as the two types of variants in previous studies. Materials and Methods: Fetal membranes were obtained by simple random sampling after full term normal deliveries at CMH Kharian. The tissue was preserved and fixated in 12% formalin solution. Gross morphology was done to find out variants with values ≤ 5%. Data analysis was done by using SPSS 20. Results: Qualitative variants of fetal membranes were considered. The attachment sites as variants were found to be on extension beyond disc margin up to 5% and as partially circumscribed up to 1%. 4% variants of membranes were found to be opaque. No incomplete membranes were found among hundred placentae. Vessels in the membranes were present among 6% of placentae which is more than 5% of the variant. Conclusion: The variants dispense an altered phenomena which may be taken as a hallmark for future investigations. Keywords: amnion, chorion, extraembryonic, fetal membranes, placenta.